Library Users' Perception of Front Office Service Experience Based on User Experience Mode at Andalas University Library - Mulhairi Mulhairi; Elva Rahmah (Darul Yasin Al Sys, 2026)
User experience plays an important role in improving library service quality, particularly in front office services as the main point of interaction between users and the library. This study aims to describe users’ perceptions of front office service experiences at the Andalas University Library based on the User Experience model, which includes five dimensions: usability, usefulness, accessibility, desirability, and satisfaction. A quantitative approach with a descriptive design was employed, involving 100 respondents selected through incidental sampling. Data were collected using questionnaires and analyzed using descriptive statistics with SPSS. The findings reveal that all user experience dimensions were categorized as high, with average scores for usability (3.57), usefulness (3.32), accessibility (3.56), desirability (3.50), and satisfaction (3.53), and an overall achievement level of 88.86%, classified as very good. These results indicate that front office services have delivered positive user experiences in terms of ease of use, environmental comfort, accessibility, and interaction quality with staff. The study concludes that the front office services at the Andalas University Library operate effectively and efficiently in meeting user needs. This study contributes to academic library service quality literature by providing empirical insight into user experience-based service evaluation. Practically, the findings imply the need for continuous improvement, particularly by enhancing usability, simplifying service procedures, and optimizing service systems to achieve more advanced and user-centered library services.